Atorvastatin desensitizes β-adrenergic signaling in cardiac myocytes via reduced isoprenylation of G-protein γ-subunits - Mühlhäuser, Ulrike; Zolk, Oliver; Rau, Thomas; Münzel, Felix; Wieland, Thomas; Eschenhagen, Thomas (The FASEB journal, 2006)
Statins exert pleiotropic, cholesterol-independent effects by reducing isoprenylation of monomeric GTPases. Here we examined whether statins also reduce isoprenylation of gamma-subunits of heterotrimeric G-proteins and thereby affect beta-adrenergic signaling and regulation of force in cardiac myocytes. Neonatal rat cardiac myocytes (NRCM) were treated with atorvastatin (0.1-10 micromol/l; 12-48 h) and examined for adenylyl cyclase regulating G-protein alpha- (Galpha), beta- (Gbeta), and gamma- (Ggamma) subunits and cAMP accumulation. Engineered heart tissue (EHT) from NRCM was used to evaluate contractile consequences. In atorvastatin-treated NRCM, a second band of Ggamma3 with a lower apparent molecular weight appeared in cytosol and particulate fractions that was absent in vehicle-treated NRCM, but also seen after GGTI-298, a geranylgeranyl transferase inhibitor. In parallel, Gbeta accumulated in the cytosol and total cellular content of Galphas was reduced. In atorvastatin-treated NRCM, the cAMP-increasing effect of isoprenaline was reduced. Likewise, the positive inotropic effect of isoprenaline was desensitized and reduced after treatment with atorvastatin. The effects of atorvastatin were abolished by mevalonate and/or geranylgeranyl pyrophosphate, but not by farnesyl pyrophosphate or squalene. Taken together, the results of this study show that atorvastatin desensitizes NRCM to beta-adrenergic stimulation by a mechanism that involves reduced isoprenylation of Ggamma and subsequent reductions in the cellular content of Galphas.